Single-side J-integral method for interfacial cracks. (1st April 2022) - Li, Wen; Huang, Peiyan; Chen, Zhanbiao; Yao, Guowen; Chen, Daiheng
Highlights: A single-side J-integral method for interfacial cracks was proposed. A ΔJ criterion for interfacial crack unstable propagation was established. Local interfacial crack propagation direction can be predicted by this method. Abstract: To evaluate the debonding failure behavior of the interface between two materials, such as a fiber reinforced polymer (FRP)–concrete interface, accurately and conveniently, a single-side J-integral method was proposed in which a path is only established on one side (concrete side) of an interfacial crack. A ΔJ criterion was established to identify the unstable propagation of an interfacial crack considering the influence of the nearby concrete cracks and interface mismatch phenomenon on the single-side J-integral. For validation, double-shear tests of fully bonded FRP–concrete specimens were carried out, with different pre-crack lengths (0, 20, 40, and 60 mm). The displacement field of the concrete surface was obtained by the digital image correlation (DIC) method. The single-side J-integral of the interfacial crack was calculated by a self-designed calculation program, and the J-integral–displacement curves were obtained. The calculation results of 14 integral paths for four kinds of specimens showed that the relative error was 15.8% between the mean absolute value of the critical ΔJ and the critical energy release rate Gside-C of the interfacial crack on the concrete side. Therefore, with the proposed method, not only the debonding failure of the interface and local crack propagation direction can be predicted, but the concrete cracks inside the J-integral paths can also be identified.